A66 ABNORMAL THYROID FUNCTION IN CHILDREN WITH CELIAC DISEASE AT DIAGNOSIS AND FOLLOW-UP IN MANITOBA. (1st March 2018) - Deora, V; EL-MATARY, W
Abstract: Background: The increased prevalence of autoimmune disorders in patients with celiac disease, including thyroid disorders, has been previously reported. However, data on abnormal thyroid function in children with celiac disease are limited. Aims: The aims of this study were to: 1) Determine the prevalence of abnormal thyroid functions in children with known celiac disease (CD) in Manitoba; at diagnosis, as well as at 6 and 18 months post diagnosis. 2) Examine predictive factors for abnormal thyroid function in celiac patients. Methods: Children (<17 years) with CD had anti-tissue transglutaminase (TtG) IgA antibody titers, and thyroid function (TSH and T4) measured at diagnosis, 6 and 18 months after diagnosis. Histopathological changes of the small intestine at diagnosis were documented using modified Marsh classification. Abnormal thyroid function tests were defined following laboratory normal values for TSH (0.7 – 5.7 mU/L) and T4 (8.0 – 20.8 pmol/L). Results: 140 children with CD [mean age; 7.8 ± 4.01 years, 87 (62.1%) girls] were consecutively enrolled. Over the study period, ten (7.1%) patients with celiac disease had abnormal thyroid function. Out of those 10 patients, three (30%) had abnormal thyroid function at diagnosis and seven (70%) after 6 and 18 months post-diagnosis. Serum TtG IgA antibody titers at diagnosis and follow-ups had no correlation with thyroid abnormalities. However, there was a significant association between histopathological changes at diagnosis and prevalence of abnormal thyroid function (p <0.05; OR=4.8; 95% C.I=1.071–23.414). Conclusions: Approximately 7% of children with CD had abnormal thyroid functions over 18 months of follow-up in Manitoba. The degree of villous atrophy at diagnosis was significantly associated with abnormal thyroid function. Several children with CD had abnormal thyroid function at follow-up with almost no clinical symptoms such as goiter. This observation highlights the importance of measuring thyroid function tests on annual bases. Funding Agencies: The Children's Hospital Research Institute of Manitoba